Lithium Therapy in Old Age: Recommendations from a Delphi Survey - Christl, Julia; Müller-Oerlinghausen, Bruno; Bauer, Michael; Kamp, Daniel; Fußer, Fabian; Benninghoff, Jens; Fehrenbach, Rosa A.; Lange-Asschenfeldt, Christian; Rapp, Michael; Ibach, Bernd; Schaub, Rainer; Wollmer, Axel; Strotmann-Tack, Timm; Hüll, Michael; Biermann, Susanne; Roscher, Katharina; Meissnest, Bernd; Menges, Alexander; Weigel, Bernd; Maliszewski-Makowka, Dorothee; Mauerer, Christian; Schaefer, Martin; Joachimsmeier, Beate; Kayser, Sarah; Rump, Lars Christian; Supprian, Tillmann (Pharmacopsychiatry, 2023)
Introduction While lithium (Li) has been well established for the treatment of bipolar disorder, geriatric patients require special attention when it comes to issues of drug safety. Declining renal function, amongst other medical conditions, and polypharmacy may pose increased risks. Only a few previous studies have addressed the management of Li in geriatric patients.Methods Twenty-four German medical experts on geriatric medicine and Li treatment participated in a Delphi survey, consisting of two rounds of questionnaires and a final formulation of treatment recommendations. Three major issues of Li therapy were outlined: initiation of treatment, monitoring of ongoing therapy, and withdrawal due to medical reasons. Final recommendations were consented to at a threshold of at least 80% expert agreement.Results Final consensus was achieved on 21 clinical recommendations. The approved recommendations covered aspects of necessary laboratory checks, concomitant medication, and target Li serum concentration in geriatric patients. Concerning the termination of Li therapy, an agreement was reached on the appropriate time span for tapering and on potential alternatives to Li. No consensus was achieved on whether concomitant dementia or frailty should be considered contraindications for Li treatment and the appropriate threshold of the estimated glomerular function rate for withdrawing Li.Conclusion According to the view of German experts, Li may be used in geriatric patients, but it should be monitored carefully. However, the lack of consent in several specific treatment situations underlines the need for research on specific issues of Li therapy.
Keywords: lithium; old age; maintenance therapy; reference serum level; drug monitoring; geriatric patients; withdrawal; renal function